Diagnóstico del clima organizacional en el Gobierno Autónomo Descentralizado del Cantón Catamayo 2019 - Burí Guamán, Lesly Karolina (2020)
he purpose of this research work is to make a diagnosis of the Organizational Climate (OC) in the GAD of Catamayo 2019, for which the following objectives were raised in this research, which are to identify the Organizational Climate factors and the factors that positively influence and negatively in the GAD of Catamayo through a quantitative investigation, using as an instrument EDCO Organizational Climate Scale applied to a population of 398 people, resulting in a score of 144.9 which in percentage would be 78.37% which places the work environment at an average level, showing a medium commitment of the staff towards the organization, the factors with a positive influence with 86% being the availability of resources, stability and 83% sense of belonging in the Autonomous Decentralized Government of Catamayo and the factor that should be improved dating with a percentage 29% collective values, 28% in terms of management style, 26% r etribution and 2% in interpersonal relationships, finally it is concluded the importance of the recognition to the personnel for the effort carried out and the possibility of carrying out action plans, they will manage to raise the level of the OC in the Catamayo Municipal GAD.